The Impact of Environmental Performance on Environmental Disclosure and Detailed Environmental Reporting in Companies - Arbin, Adhia; Rohmatika, Rillita (Advances in Environmental Innovation, 2024)
Objective: This study aims to explore the impact of Environmental Performance on Environmental Disclosure and Hard Environmental Disclosure among companies listed on the Indonesia Stock Exchange (IDX) from 2018 to 2023. It also examines the influence of company size, leverage, and profitability on these disclosure practices.Methods: A mixed-methods approach is employed, combining quantitative data from annual and sustainability reports with PROPER ratings. The analysis utilizes multiple regression to assess the relationships between Environmental Performance, Environmental Disclosure, and Hard Environmental Disclosure, with classical assumption tests conducted to ensure the validity of the regression model.Results: The analysis reveals that higher Environmental Performance is positively associated with increased Environmental Disclosure. Additionally, more comprehensive Environmental Disclosure correlates with more detailed Hard Environmental Disclosure. Among the control variables, Company Size and Profitability significantly affect both Environmental Disclosure and Hard Environmental Disclosure, while Leverage does not show a significant impact.Novelty: This study advances the understanding of how Environmental Performance influences disclosure practices in Indonesian firms and highlights the role of company-specific factors such as size and profitability in shaping the extent and detail of environmental reporting.Implication: The findings suggest that improving Environmental Performance can lead to more extensive and detailed Environmental Disclosure. For policymakers and practitioners, this underscores the need for strategies and regulations that promote transparent environmental reporting, particularly considering the varying impacts of company size and profitability.